Pelatihan Akuaponik Kepada Masyarakat Kampung Krasak Kota Baru, Gondokusuman, Yogyakarta - Emaputra, Andrean; Sulistyaningsih, Eka; Khasanah, Rahayu; Budhyaty, Arifah (DHARMA BAKTI, 2024)
Aquaponics is a method for cultivating fish and vegetables at the same time. This method can increase family food security, such as by utilizing fish ponds or limited land. West Krasak Village is a residential area located in the center of Yogyakarta city with limited land conditions. Therefore, the village community needs to receive training on implementing aquaponics in their environment to utilize limited land and increase family food security. This training involved a team of lecturers and students from Universitas AKPRIND Indonesia. This training lasted for 3 hours, starting with introductions of team members, delivery of material, practice of aquaponic installation in front of the participants, distribution of chili seeds to the participants, and installation of aquaponic samples directly in one of the residents' ponds. This activity received extraordinary enthusiasm from residents and was able to increase public knowledge about this matter. Chili seeds measuring 10 cm can also be planted directly by the community. It is hoped that this activity can become a model for the community around West Krasak Village so that aquaponics can become a positive side activity for residents that produces positive results of fish and vegetables.